2018
DOI: 10.1002/alr.22078
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction and cognition among older adults in the United States

Abstract: Objectively measured olfactory dysfunction is independently associated with cognitive impairment. These findings are consistent with previous studies and suggest the utility of objective olfactory tests as an indicator for cognitive impairment as compared with self-reported olfactory dysfunction, which is an uncertain indicator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Our study further supports the previous literature that has developed the association between OD and cognitive dysfunction. 19,3640 This association continued to be present when controlling for potential demographic and comorbid factors, including concomitant GD, which represents a novel finding. Furthermore, our analyses revealed that cognitive dysfunction was associated with OD, regardless of the severity of dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…Our study further supports the previous literature that has developed the association between OD and cognitive dysfunction. 19,3640 This association continued to be present when controlling for potential demographic and comorbid factors, including concomitant GD, which represents a novel finding. Furthermore, our analyses revealed that cognitive dysfunction was associated with OD, regardless of the severity of dysfunction.…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of olfactory dysfunction is high, at 24-75% among older adults, and increases substantially with age [1]. It is an important clinical symptom indicative of an early stage of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), dementia with Lewy bodies, and frontotemporal lobar degeneration, with neuropathologic changes in the olfactory epithelium, the olfactory bulb/tract, primary olfactory cortices, their secondary targets, and the olfactory circuitry [2].…”
Section: Introductionmentioning
confidence: 99%
“…As would be expected based on their declining olfactory sensory abilities, studies show clear impairment in odor identification among older persons (Hummel et al, 1997;Larsson et al, 2000;Larsson et al, 2004;Hedner et al, 2010;Olofsson et al, 2010;Wong et al, 2010;Makowska et al, 2011;Schubert et al, 2011;Wehling et al, 2011;Wilson et al, 2011;Menon et al, 2013;Kern et al, 2014;Pinto et al, 2014). Prevalence rates for olfactory dysfunction, based on cued odor identification, increase from 11 to 24% in middle-aged individuals to 37 to 70% at the age of 70 years (Murphy et al, 2002;Brämerson et al, 2004; see also Hoffman et al, 2016;Seubert et al, 2017;Choi et al, 2018). Results from longitudinal studies suggest that these findings cannot simply be attributed to cohort effects (Schubert et al, 2011;Wehling et al, 2016a).…”
Section: Introductionmentioning
confidence: 93%
“…A vast number of studies with older participants have demonstrated impaired olfactory functions (Hummel et al, 1997;Larsson et al, 2000;Stuck et al, 2006;Hedner et al, 2010;Kern et al, 2014;Choi et al, 2018;Schubert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%